Risk factors for developmental quotients in ASD children: A cross-sectional study - Dong, Han-Yu; Miao, Chun-Yue; Zhang, Yu; Shan, Ling; Feng, Jun-Yan; Jia, Fei-Yong; Du, Lin (Frontiers in Psychology, 2023)
Abstract We aim to analyze the risk factors for developmental quotients (DQs) in children with autism spectrum disorder (ASD) and better understand the effects of screen time on neurodevelopment in children with ASD. We retrospectively analyzed the data of 382 children with ASD, including demographic profiles; socioeconomic status; score on the Chinese parent–child interaction scale (CPCIS); screen time questionnaire; ASD symptom rating scales, including the Autism Behavior Checklist, Childhood Autism Rating Scale, and Autism Diagnostic Observation Schedule; and DQs using Griffiths Development Scales–Chinese Edition. Univariate analysis was carried out to analyze the factors related to the DQs of children with ASD, and a linear regression model was used to identify the independent influencing factors of the DQs of children with ASD. We conclude that vitamin D status, the severity of autistic symptoms, and parent–child interaction are risk factors for developmental quotients in children with ASD. Screen time is negatively associated with DQs in children with ASD but is not an independent risk factor for DQs.